Alpha 1 adrenergic receptor-mediated inflammatory responses in human testicular peritubular cells - Rossi, Soledad Paola (2018)
Stress activates the sympathetic nervous system and is linked to impaired fertility in man. We hypothesized that catecholamines by acting on testicular cells have a role in these events, possibly by fostering an inflammatory environment. The cells of the wall of seminiferous tubules, human testicular peritubular cells (HTPCs), express adrenergic receptors (ADRs) α1B, α1D, β1 and β2. A selective α1-ADR agonist, phenylephrine, increased intracellular Ca 2+ -levels in cultured HTPCs and induced COX-2, IL-6 and MCP-1 mRNA expression without affecting IL-1β mRNA. These changes were paralleled by a significant increase in the secretion of IL-6 and MCP-1. Epinephrine was also effective, but salbutamol, a selective β2-ADR agonist was not. Our results suggest that stress-associated elevation of catecholamines may be able to promote inflammatory events by targeting peritubular cells in the human testis. Blockage of α1-ADRs may therefore be a novel way to interfere with stress-related impairment of male reproductive functions.